Determining the composition of small features in atom probe: bcc Cu-rich precipitates in an Fe-rich matrix - Morley, A; Sha, G; Hirosawa, S; Cerezo, A; Smith, G (Elsevier, 2009)
Aberrations in the ion trajectories near the specimen surface are an important factor in the spatial resolution of the atom probe technique. Near the boundary between two phases with dissimilar evaporation fields, ion trajectory overlaps may occur, leading to a biased measurement of composition in the vicinity of this interface. In the case of very small second-phase precipitates, the region affected by trajectory overlaps may extend to the centre of the precipitate prohibiting a direct measurement of composition. A method of quantifying the aberrant matrix contribution and thus estimating the underlying composition is presented. This method is applied to the Fe-Cu-alloy system, where the precipitation of low-nanometre size Cu-rich precipitates is of considerable technical importance in a number of materials applications. It is shown definitively that there is a non-zero underlying level of Fe within precipitates formed upon thermal ageing, which is augmented and masked by trajectory overlaps. The concentration of Fe in the precipitate phase is shown to be a function of ageing temperature. An estimate of the underlying Fe level is made, which is at lower levels than commonly reported by atom probe investigations.